Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content• Using Advanced Artificial Intelligence Technologies to Improve Institutional Performance in Business Associations in RiyadhMs. Mona Jeza Almutairi,  Mr. Hassan Khidhr Alhallafi, Mr. Almotasim Khalil Alabbas• Applying lEAN Management Methods and Role to Achieving Administrative and Financial Performance in Business Organizations (Field Study)Asst-Prof. Dar Elneim Abakr Mohamed, Prof. Hoda Diab Ahmed• The Impact of Talent Management on Organizational Health: An Applied Study on Workers in the Emirate of Jazan RegionMr. Ghazwani, Ahmed Hassan, Prof. Alariki, Baseim Qaid• The Role of Strategic Management in Achieving Sustainable Development GoalsMs. Ibtesam Ahmed Al-Malkie, Co-Porf. Hasan Ahmed Al-Tally• Administrative leadership and its relationship to strengthening governance in local bodies in the Palestinian governorate of QalqilyaLecturer \ Ala’ Yousef Najib Ashour• The impact of Technological development on the Growth of the manufacturing sector  in gulf cooperation council countries Ms. Razan Mansour Hassan Almaiman, Co-Prof. Vivian Mohammed Saleh Nasrulddin• The Role of E-Government in combating Corruption in SyriaLawyer \ Animar Ali Zaher
Keywords: The Journal of Economic, Administrative and Legal Sciences